The diversity of medicinal plant resources in Kampung Batu Ring-Kampung Beng: A case study of Lenggong Valley, World Heritage Site - Abd Aziz, Siti Hajar; Zakaria, Zuraini (2013)
This ethnomedical survey was conducted in Kampung Batu Ring, part of the small villages included in Kampung Beng, a village commercialized and well known as one of the Homestay villages established in Lenggong District, Hulu Perak. The documentation focuses on the diversity of medicinal plants, its use and dependency of people in Kampung Batu Ring on herbal remedies. The richness of the biodiversity and cultural heritage of Kampung Batu Ring makes it more attractive as a potential traditional village to be commercialized in the tourism aspect. Geographically, it is located in the Piah Reserve Forest valley and mountains in the mid of Banjaran Titiwangsa. Data was obtained from the villagers of fifty most common wild plant species used in daily life in terms of cooking and healthcare. Most of the herbs used are harvested from the forests and being planted around their homeland. The remedies are used internally and externally for treating various ailments from common stomach ache to severe high blood pressure and diabetes. There are several species being consumed as salads especially those which are renown for anti-aging purposes. The practices on the utilization and consumption of these plants in the daily life of the villagers are traditionally transmitted from their great ancestors. Thus, these plant benefits are found to be well known amongst the elderly.